Developing Communicative Digital Literacy in the Study of Digital Media Fundamentals - Denny Setiawan Batubara; Tuty Mutiah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The development of information and communication technology has triggered a significant transformation in the way individuals and societies communicate. Digital media has not only become a channel for message delivery but also shapes the way people think, interact, and construct social meaning. In this context, digital literacy should not be understood merely as the technical ability to use digital devices, but also as a communicative competence that involves critical understanding of content, context, and the impact of digital communication. This article aims to fundamentally examine the role of digital media in shaping communicative digital literacy and how this concept becomes an essential part of contemporary communication studies. Through a qualitative-descriptive approach and literature review, this study maps the conceptual framework of digital media from a communication science perspective, including the shift from one-way communication to interactive and participatory communication models. The article also discusses the role of digital media in mediating social relationships, meaning-making processes, and identity formation in digital spaces. Communicative digital literacy is emphasized as the ability not only to access and disseminate information but also to understand the dynamics of digital communication ethically, critically, and reflectively. The findings show that understanding the fundamentals of digital media—including the characteristics of digital mediation, algorithms, and patterns of virtual interaction—is an essential component in developing communicative digital literacy. The main contribution of this article is to provide a theoretical foundation for designing adaptive, critical, and inclusive communication strategies in the digital era. Thus, strengthening digital literacy from a communication science perspective becomes a strategic step in addressing the increasingly complex communication challenges of the digital society.